The Complete Guide to Designing a Mobile App - Percival, Rob; Philippi, Reneta (Packt Publishing, 2019)
Build your audience with professionally designed, UX-friendly apps About This Video Learn basic design principles and tools and work on three brilliant projects Learn the basics of prototyping In Detail Welcome to The Complete Guide to Designing a Mobile App! Many fantastic apps never attract a big audience, and one key reason for that is that they're poorly designed. There's a big difference between building an app and designing it; it's the difference between an app that works perfectly, looks fantastic, and does exactly what it promises, and one that doesn't. The more design work you put into your app, the more successful your app will be. In this course, you'll get a brief overview of design principles, before getting into the how-to and learning by doing, with regular exercises and challenges to test and cement your learning. The first half of the course focuses on: Design basics-Learn simple (but devastatingly effective) design principles. Understand the differences between iOS and Android design systems, and what that means for your app. Polishing your idea-Tailor your app to your users and stand out from the competition! Learn how to sketch out and wireframe an app idea and see the difference this makes! Information architecture-The backbone of any good app. The structure of your design is so important-learn the guiding principles behind the app and information architecture here! Style-color, font, icons, typography. Everything you need to know! Components and patterns-Help users navigate your app. Create forms, fields, notifications, animations, and more! The user experience-Make your app simple and intuitive and your users will love you. Learn how here. Design with Sketch-A complete guide to the hugely well-regarded design software, Sketch. As your skills increase and your confidence grows, you'll start work on three brilliant projects, designing and creating every element of the following apps! An Instagram app A food delivery app A studio booking app By the end of this course, you'll know everything there is to know about app design and will have created three hugely impressive projects for your career portfolio!
Online resource; Title from title screen (viewed October 18, 2019)
Keywords: iOS (Electronic resource); Android (Electronic resource); Mobile apps; Application software -- Development; Applications mobiles; Logiciels d'application; Développement; Electronic videos